High-thermal-conductivity magnesium alloy capable of being molded at room temperature, preparation method thereof and cookware
Through the design of the magnesium alloy composition, select the appropriate alloying element and ratio, weaken the plate weaving of the magnesium alloy, solve the problem of poor plastic processing capacity of magnesium alloy at room temperature, and realize the good room temperature of the magnesium alloy. The high thermal guidance rate has improved its application competitiveness in the kitchenware market.
Patent Information
- Application Number
- CN202411501312.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The poor plastic processing capacity of magnesium alloy materials at room temperature has led to the current use of hot stamping method, which increases processing costs and poses production safety risks, hindering the application of magnesium alloys in the kitchenware market.
Through the design of the magnesium alloy ingredients, the alloying elements such as CA, Zn and MN are selected, and a reasonable ratio can make the solid -soluble atoms partial after the annealing.
The good room temperature of the magnesium alloy can be achieved. The ejaculation value of the Eriksen Cup can reach more than 7.8mm, which significantly reduces the production cost and increases the room temperature thermal guidance rate of the magnesium alloy. Competitiveness.
Smart Images

Figure CN119372531A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of magnesium alloy materials, and in particular to a high thermal conductivity magnesium alloy that can be formed at room temperature, a preparation method thereof, and a cookware. Background Art
[0002] The density of magnesium is about 1.8 g / cm 3 , by comparison, the density of aluminum is 2.7 g / cm 3 , the density of iron is 7.8g / cm 3 The thermal conductivity of magnesium is 156W / mK, the thermal conductivity of aluminum is 237W / mK, and the thermal conductivity of iron is 36W / mK. Most importantly, magnesium is safe and non-toxic and has been widely used in medical implant materials. Therefore, compared with the iron and aluminum materials currently used in the kitchenware industry, magnesium, which has the characteristics of light weight, good thermal conductivity, safety and non-toxicity, is very suitable for kitchenware materials.
[0003] When making cookware, the usual process is to stamp the sheet to achieve the forming. However, magnesium alloy materials have poor plastic processing ability at room temperature, and using room temperature stamping often causes the sheet to crack. Therefore, hot stamping is currently mainly used to form magnesium alloy cookware. During stamping, both the mold and the sheet need to be heated to above 300°C, which not only greatly increases the processing cost, but also easily causes production safety hazards. Since aluminum alloy sheets can be formed at room temperature, the processing cost is lower than that of magnesium, which hinders the application of magnesium alloys in the kitchenware market. Summary of the invention
[0004] The object of the present application is to provide a high thermal conductivity magnesium alloy with good room temperature formability.
[0005] To achieve the above-mentioned purpose, the present application provides a high thermal conductivity magnesium alloy that can be formed at room temperature in the first aspect, which is composed of the following elemental components in mass percentage: Ca 0.5% to 3%, Zn 0.5% to 3%, Mn 0.5% to 3%, and the balance is magnesium and unavoidable impurities ≤ 0.05%. The present application designs the composition of the magnesium alloy, firstly selects the alloying elements that have the least effect on the thermal conductivity of magnesium, and then selects the appropriate alloying elements and proportions, so that the solid solution atoms will be segregated at the grain boundaries after annealing, so as to weaken the sheet texture of the magnesium alloy, so that the magnesium sheet is more likely to initiate multi-system slip when deformed, thereby greatly improving the machinability of the magnesium alloy, so that it has good room temperature thermal conductivity and formability.
[0006] In some embodiments of the present application, the alloy is composed of the following elemental components in mass percentage: Ca 0.5% to 1%, Zn 0.5% to 1.5%, Mn 0.5% to 1.5%, and the balance is magnesium and unavoidable impurities ≤ 0.05%.
[0007] The second aspect of the present application provides a method for preparing the above-mentioned high thermal conductivity magnesium alloy that can be formed at room temperature, comprising: calculating the ratio of alloy raw materials according to the elemental composition; heating the alloy raw materials to melt under the condition of protective gas, and casting the alloy raw materials after they are smelted and mixed into molten metal; subjecting the obtained alloy ingots to homogenization heat treatment, hot extrusion treatment and rolling treatment in sequence to obtain alloy plates; cutting the alloy plates into target sizes and annealing them to obtain the high thermal conductivity magnesium alloy that can be formed at room temperature.
[0008] In some embodiments of the present application, the alloy raw materials include pure magnesium, magnesium-calcium master alloy, pure zinc, and magnesium-manganese master alloy.
[0009] In some embodiments of the present application, the protective gas is a mixed gas of CO2 and SF6 or a mixed gas of argon and SF6; the heating temperature of the alloy raw material is 680°C to 720°C.
[0010] In some embodiments of the present application, the temperature of the homogenization heat treatment is 400° C. to 450° C., and the time is 12 hours to 24 hours.
[0011] In some embodiments of the present application, the temperature of the hot extrusion treatment is 300°C to 400°C.
[0012] In some embodiments of the present application, the temperature of the rolling process is 300°C to 350°C.
[0013] In some embodiments of the present application, the annealing temperature is 300° C. to 400° C., and the annealing time is 0.25 hour to 1 hour.
[0014] A third aspect of the present application provides a cookware, wherein the cookware body is formed by stamping the above-mentioned high thermal conductivity magnesium alloy that can be formed at room temperature at room temperature.
[0015] Compared with the prior art, the room temperature formable high thermal conductivity magnesium alloy of the present application has the following beneficial effects:
[0016] The present application designs the composition of magnesium alloy so that the magnesium alloy has good room temperature formability, and the Ericsson cupping value at room temperature can reach more than 7.8mm, which can be directly stamped at room temperature, effectively solving the problem of poor plastic processing ability of magnesium alloy materials at room temperature, breaking through the limitation of hot stamping method currently used to form magnesium alloy cookware, and significantly reducing production costs. At the same time, the magnesium alloy of the present application has high thermal conductivity, and its room temperature thermal conductivity can be as high as 120W / (m·K), which can be increased by 50% compared with commercial AZ31 magnesium alloy. It can be seen that the high thermal conductivity magnesium alloy that can be formed at room temperature in the present application can greatly improve the application competitiveness of magnesium alloy in the kitchenware market. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The following drawings describe in detail the exemplary embodiments disclosed in this application. The same reference numerals represent similar structures in several views of the drawings. Those skilled in the art will understand that these embodiments are non-limiting, exemplary embodiments, and the drawings are only used for the purpose of illustration and description, and are not intended to limit the scope of this application. Other embodiments may also accomplish the inventive intent in this application. It should be understood that the drawings are not drawn to scale. Among them:
[0018] Figure 1 This is a photo of a pot body obtained by stamping the magnesium alloy prepared in Example 1 of the present application at room temperature;
[0019] Figure 2 This is a photo of a pot body obtained by stamping the magnesium alloy prepared in Comparative Example 1 of the present application at room temperature;
[0020] Figure 3 The backscattered electron diffraction pattern of the magnesium alloy prepared in Example 1 of the present application;
[0021] Figure 4 The result diagram of the Erichsen cupping test of the magnesium alloy prepared in Example 1 and Comparative Example 1 of the present application;
[0022] Figure 5 It is a schematic diagram comparing the results of the Erichsen cupping test and the thermal conductivity test of Example 1 of the present application, Comparative Example 1 and some existing magnesium alloys. DETAILED DESCRIPTION
[0023] The following description provides specific application scenarios and requirements of the present application, with the purpose of enabling those skilled in the art to make and use the content in the present application. It will be apparent to those skilled in the art that various local modifications to the disclosed embodiments are apparent, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the present application. Therefore, the present application is not limited to the embodiments shown, but to the widest scope consistent with the claims.
[0024] The present application provides a high thermal conductivity magnesium alloy that can be formed at room temperature, which is composed of the following elemental components in mass percentage: Ca 0.5% to 3%, Zn 0.5% to 3%, Mn 0.5% to 3%, and the balance is magnesium and unavoidable impurities ≤ 0.05%. When this elemental composition is used, during the rolling annealing process, the solid solution atoms will be segregated at the grain boundaries. This segregation will reduce the mobility of the grain boundaries and change the energy difference between special grain boundaries and random grain boundaries. As the segregation increases, the orientation relationship of the preferential growth of magnesium alloy grains will change, resulting in a weakening of the texture. Texture weakening means that it is easier for magnesium alloy sheets to initiate multi-system slip when deformed. Generally, the deformation of magnesium alloys is carried out in a The basal slip and twinning are completed. However, the segregation of solid solution atoms will activate more slip systems, such as<c+a> The conical slip system makes it easier for the alloy to deform evenly during plastic processing. Texture weakening and the initiation of multi-system slip have a positive effect on the machinability of magnesium alloy sheets. First, texture weakening can reduce the anisotropy of magnesium alloys during deformation, thereby improving their forming properties. Secondly, the initiation of multi-system slip can enable the alloy to disperse stress more effectively during deformation, avoid local stress concentration, and thus improve its deformation resistance. At the same time, the elemental composition of the present application also unexpectedly makes the magnesium alloy have high thermal conductivity. This makes the magnesium alloy of the present application fully meet the application requirements of kitchenware materials, breaking through the application limitations of magnesium alloys in the kitchenware market.
[0025] In the present application, the mass percentages of Ca, Zn and Mn can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, or any point value within the subrange composed of the above specific numerical values.
[0026] In some preferred embodiments, the room temperature formable high thermal conductivity magnesium alloy is composed of the following elemental components in mass percentage: Ca 0.5% to 1%, Zn 0.5% to 1.5%, Mn 0.5% to 1.5%, and the balance is magnesium and unavoidable impurities ≤ 0.05%.
[0027] In some preferred embodiments, the room temperature formable high thermal conductivity magnesium alloy is composed of the following elemental components in mass percentage: Ca 0.8%, Zn 1%, Mn 1%, and the balance being magnesium and unavoidable impurities ≤ 0.05%.
[0028] The present application also provides a method for preparing the above-mentioned high thermal conductivity magnesium alloy that can be formed at room temperature, comprising the following steps:
[0029] S1: Calculate the ratio of alloy raw materials according to element composition;
[0030] S2: heating the alloy raw materials to melt under the condition of protective gas, and casting after the alloy raw materials are melted and mixed into molten metal;
[0031] S3: sequentially subjecting the obtained alloy ingot to homogenization heat treatment, hot extrusion treatment and rolling treatment to obtain an alloy plate;
[0032] S4: cutting the alloy sheet into a target size and annealing the alloy sheet to obtain the high thermal conductivity magnesium alloy that can be formed at room temperature.
[0033] In some preferred embodiments, in step S1, the alloy raw materials include pure magnesium, magnesium-calcium master alloy, pure zinc, magnesium-manganese master alloy.
[0034] In some preferred embodiments, in step S2, the protective gas is a mixed gas of CO2 and SF6 or a mixed gas of argon and SF6; the heating temperature of the alloy raw material is 680°C to 720°C.
[0035] In some preferred embodiments, in step S3, the temperature of the homogenization heat treatment is 400° C. to 450° C., and the time is 12 hours to 24 hours.
[0036] In some preferred embodiments, in step S3, the temperature of the hot extrusion treatment is 300°C to 400°C.
[0037] In some preferred embodiments, in step S3, the temperature of the rolling process is 300°C to 350°C.
[0038] In some preferred embodiments, in step S4, the annealing temperature is 300° C. to 400° C., and the annealing time is 0.25 hour to 1 hour.
[0039] The present application also provides a cookware, the pot body of which is formed by room temperature stamping of the above-mentioned high thermal conductivity magnesium alloy that can be formed at room temperature.
[0040] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solution of the present application. Unless otherwise specified, the reagents and raw materials used can be purchased through commercial channels. The experimental methods in the following examples that do not specify specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0041] Example 1
[0042] This embodiment provides a high thermal conductivity magnesium alloy, which is composed of the following element components in percentage by mass: Ca 0.8%, Zn 1%, Mn 1%, and the balance being magnesium and unavoidable impurities ≤ 0.05%.
[0043] This embodiment also provides a method for preparing the high thermal conductivity magnesium alloy, comprising the following steps:
[0044] (1) Calculating the mass of pure aluminum, magnesium-30wt.% calcium master alloy, and pure zinc, magnesium-30wt.% manganese master alloy according to the elemental composition and weighing them for later use;
[0045] (2) Under the protection of a mixed gas of CO2 and SF6 with a volume ratio of 50:1, the raw materials are smelted at 700°C, and after they are completely melted into molten metal, the molten metal is gravity cast;
[0046] (3) subjecting the obtained alloy ingot to homogenization heat treatment at a temperature of 400° C. for 12 hours;
[0047] (4) hot extrusion treatment at a temperature of 300°C to extrude the alloy into an alloy plate with a thickness of 11 mm;
[0048] (5) rolling the alloy plate at a temperature of 300° C. to obtain a plate having a thickness of 3 mm;
[0049] (6) The rolled sheet is cut into required sizes and then annealed at 300°C for 0.25 hours.
[0050] This embodiment also provides a cooker, wherein the cooker body is formed by stamping the high thermal conductivity magnesium alloy prepared in this embodiment at room temperature (25°C). Figure 1 As shown, the pot body has a standard shape, and the surface of the pot body is intact without cracks. Therefore, the high thermal conductivity magnesium alloy prepared in this embodiment has good room temperature formability.
[0051] Example 2
[0052] This embodiment provides a high thermal conductivity magnesium alloy, which is composed of the following elemental components in the following mass percentages: Ca 3%, Zn 1%, Mn 1%, and the balance being magnesium and unavoidable impurities ≤ 0.05%.
[0053] The preparation method of the high thermal conductivity magnesium alloy and the cookware of this embodiment can refer to Example 1.
[0054] Example 3
[0055] This embodiment provides a high thermal conductivity magnesium alloy, which is composed of the following element components in mass percentage: Ca 0.8%, Zn 3%, Mn 3%, and the balance is magnesium and unavoidable impurities ≤ 0.05%.
[0056] The preparation method of the high thermal conductivity magnesium alloy and the cookware of this embodiment can refer to Example 1.
[0057] Comparative Example 1
[0058] This comparative example provides a commercial AZ31 magnesium alloy, the element composition of which is: 3% aluminum, 1% zinc, and 96% magnesium.
[0059] The preparation method of the commercial AZ31 magnesium alloy and the cookware of this embodiment can refer to Example 1. The pot body of the cookware is as follows: Figure 2 As shown, the shape of the pot body does not meet the requirements and the surface of the pot body is severely cracked. Therefore, the room temperature formability of commercial AZ31 magnesium alloy is poor and cannot be formed by room temperature stamping.
[0060] Comparative Example 2
[0061] This comparative example provides a magnesium alloy, which is composed of the following elemental components in mass percentage: Ca 0.8%, Zn 3.5%, Mn 1%, and the balance is magnesium and unavoidable impurities ≤ 0.05%. The preparation method thereof can refer to Example 1.
[0062] Comparative Example 3
[0063] This comparative example provides a magnesium alloy, which is composed of the following elemental components in mass percentage: Ca 0.8%, Zn 1%, Mn 3.5%, and the balance is magnesium and unavoidable impurities ≤ 0.05%. The preparation method thereof can refer to Example 1.
[0064] Comparative Example 4
[0065] This comparative example provides a magnesium alloy, which is composed of the following elemental components in mass percentage: Ca 3.5%, Zn 1%, Mn 1%, and the balance is magnesium and unavoidable impurities ≤ 0.05%. The preparation method thereof can refer to Example 1.
[0066] Electron Backscatter Diffraction (EBSD)
[0067] The magnesium alloy prepared in Example 1 was subjected to an electron backscatter diffraction test, and the test method was as follows: the magnesium alloy sample was wire-cut into small pieces of 5 mm×5 mm×3 mm for easy observation, inlaid with conductive resin, and surface ground with 320-mesh, 1000-mesh and 2000-mesh sandpapers, respectively, and then polished with 3μm, 1μm and 0.02μm diamond suspension polishing liquids, and finally vibrated polished with 0.02μm diamond suspension polishing liquid to remove the stress layer to obtain a sample that can be used for EBSD observation, and the EBSD experiment was carried out using a TESCAN GAIA3 scanning electron microscope with a voltage of 20kV.
[0068] Figure 3 The backscattered electron diffraction pattern of the magnesium alloy prepared in Example 1 and the texture pole figure and grain size distribution diagram calculated therefrom show that, unlike the common commercial magnesium alloy sheet, the magnesium alloy sheet has a weak {0002} texture and a uniform grain size distribution, which is conducive to plastic deformation, demonstrating why the alloy has good room temperature forming ability.
[0069] Formability test
[0070] Please refer to GB / T 4156-2020 Erickson cupping test method. The measured Erickson cupping values are shown in Table 1 and Figure 5 The test results of the magnesium alloys prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 4 shown.
[0071] Thermal conductivity test
[0072] The alloy plate samples were processed into discs with a diameter of 12.7 mm. The thermal diffusivity of the alloy plate was measured using a LAF467 laser thermal conductivity tester from NETZSCH, Germany. The thermal conductivity was obtained by multiplying the measured thermal diffusivity with the density and specific heat of the alloy. The test results are shown in Tables 1 and Figure 5 shown.
[0073] Table 1 Performance test results
[0074]
[0075]
[0076] As shown in Table 1, compared with the magnesium alloys of Comparative Examples 1 to 4, the Erichsen cupping value of the magnesium alloys of the embodiments of the present application is increased to more than 7.8 mm, and the thermal conductivity is more than 110 W / (m·K). It can be seen that the present application significantly improves the room temperature formability of the magnesium alloy by adjusting the composition of the magnesium alloy, and also makes the magnesium alloy have a higher room temperature thermal conductivity.
[0077] Figure 5 The results of the Richson cupping test and thermal conductivity test of Example 1 of the present application, Comparative Example 1 and some existing magnesium alloys are shown. It can be seen that the room temperature formability of the magnesium alloy of the present application is significantly better than that of the existing magnesium alloys, and the room temperature thermal conductivity also exceeds that of the existing magnesium alloys. Although the room temperature thermal conductivity of Mg-5Zn-0.5Ca-0.4Zr is comparable to that of the magnesium alloy of the present application, its room temperature formability is very poor.
[0078] In summary, the magnesium alloy provided in the present application not only has good room temperature formability, but also has high thermal conductivity, breaking through the application bottleneck of magnesium alloy mainly formed by hot stamping, and has good application prospects in the kitchenware market.
[0079] The above description of the embodiments is to facilitate those of ordinary skill in the art to understand and apply the present application. It is obvious that those familiar with the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without having to pay creative labor. Therefore, the present application is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the contents disclosed in the present application without departing from the scope and spirit of the present application are within the scope of the present application.
Claims
1. A high thermal conductivity magnesium alloy that can be formed at room temperature, characterized in that: It is composed of the following elemental components in mass percentage: Ca 0.5% to 3%, Zn 0.5% to 3%, Mn 0.5% to 3%, and the balance is magnesium and unavoidable impurities ≤ 0.05%.
2. The room temperature formable high thermal conductivity magnesium alloy according to claim 1, characterized in that: It is composed of the following elemental components in mass percentage: Ca 0.5% to 1%, Zn 0.5% to 1.5%, Mn 0.5% to 1.5%, and the balance is magnesium and unavoidable impurities ≤ 0.05%.
3. A method for preparing a high thermal conductivity magnesium alloy that can be formed at room temperature according to claim 1 or 2, characterized in that: include: The proportion of alloy raw materials is calculated based on the elemental composition; Heating the alloy raw materials to melt under the condition of protective gas, and casting after the alloy raw materials are melted and mixed into molten metal; The obtained alloy ingot is subjected to homogenization heat treatment, hot extrusion treatment and rolling treatment in sequence to obtain an alloy plate; The alloy sheet is cut into a target size and annealed to obtain the high thermal conductivity magnesium alloy that can be formed at room temperature.
4. The method for preparing a high thermal conductivity magnesium alloy that can be formed at room temperature according to claim 3, characterized in that: The alloy raw materials include pure magnesium, magnesium-calcium master alloy, pure zinc, and magnesium-manganese master alloy.
5. The method for preparing a high thermal conductivity magnesium alloy that can be formed at room temperature according to claim 3, characterized in that: The protective gas is a mixed gas of CO2 and SF6 or a mixed gas of argon and SF6; the heating temperature of the alloy raw material is 680°C to 720°C.
6. The method for preparing a high thermal conductivity magnesium alloy that can be formed at room temperature according to claim 3, characterized in that: The homogenization heat treatment is performed at a temperature of 400° C. to 450° C. for a time of 12 hours to 24 hours.
7. The method for preparing a high thermal conductivity magnesium alloy that can be formed at room temperature according to claim 3, characterized in that: The temperature of the hot extrusion treatment is 300°C to 400°C.
8. The method for preparing a high thermal conductivity magnesium alloy that can be formed at room temperature according to claim 3, characterized in that: The rolling treatment is performed at a temperature of 300°C to 350°C.
9. The method for preparing a high thermal conductivity magnesium alloy that can be formed at room temperature according to claim 3, characterized in that: The annealing temperature is 300° C. to 400° C., and the annealing time is 0.25 hour to 1 hour.
10. A cookware, characterized in that: The pot body is formed by room temperature stamping of the high thermal conductivity magnesium alloy that can be formed at room temperature as claimed in claim 1 or 2.